Management of regional training systems - V. I. Blinov; I. S. Sergeev; E. Yu. Esenina; L. N. Kurteeva; S. A. Osadcheva (Obrazovanie i Nauka)
Introduction. Over recent years, the issues of building regional systems of human recourses development have been actively discussed in expert community. These issues are perpetually on the agenda of the Russian Federation territories (regions), despite the fact that the projects of various organisations at the federal level have been already finished or are close to completing. The projects are designed to stimulate industrial growth due to workforce recruitment of manufacturing sector by highly qualified specialists. In a number of territories (for example, the Perm Territory, the Republic of Tatarstan, the Belgorod and Tambov Regions, etc.), there are successful practices of managing the personnel training system required by regional economics. However, systemic approaches at the level of the whole country have not been developed yet. The authors of the present publication consider that the unsatisfactory socio-economic efficiency of vocational education is substantially caused by insufficient quality of its management.The aims of this article were the following: to report on the outcomes of comparative-analytical research on the content of regional development programmes of vocational education and the strategy of social and economic development of regions of the Russian Federation and to formulate proposals for the improvement of such programmes as a management tool, which provides quick response to changes of personnel needs in regions and reduction in deficit of skilled workers.Methodology and research methods. In the course of the research, the methods of the criterial and comparative analysis, goal-setting, formalisation and interpretation of results were applied. The authors conducted content analysis and necessity and sufficiency analysis of the documents and materials, which are in open access on the Internet. Programme-based and project-based approaches and mechanisms were considered as methodological base of management of the regional systems of personnel training.Results and scientific novelty. The criteria and indicators of efficiency assessment of regional development programmes of vocational education were presented and justified. The common faults and contradictions of implementation of these programmes, which are specific not only for “typical regions”, but also for some “leading regions”, were revealed and described. It is noted that, at the qualitative and quantitative level, the existing programmes cannot systemically satisfy the needs of the manufacturing sphere for the qualified experts capable to master and implement advanced technologies. The comprehensive solution to this problem demands correction and advancement of administrative activity in two rather autonomous directions – taking measures to improvement of the principles of design of the discussed programmes and their orientation to use modern approaches to the development of vocational education.Practical significance. The authors’ conclusions on the structure and programme content of vocational education development, organisational conditions of their optimisation and effectiveness are addressed to the supreme executive authorities and education governing bodies in different constituent entities of the Russian Federation.